Representative value of thermal conductivity for wickless heat pipe in a thermoelectric generator system via computational numerical analysis / Nur Faranini Zamri, Ahmad Nidhol Rahin and Muhammad Hadrami Hamdan - Zamri, Nur Faranini; Rahin, Ahmad Nidhol; Hamdan, Muhammad Hadrami (Smart Manufacturing Research Institute (SMRI), 2023)
Thermoelectric generator (TEG) cells are capable of producing electricity from the flow of heat through semiconductor materials via the Seebeck effect. A TEG module (TEM) was developed through the integration of TEG cells, heat pipes, and heat sinks with the function to recover low-temperature waste heat for combined heat and power outputs. The mechanics of heat transport through the components have a distinctive impact on overall performance. In analytical assessment, heat transfer coefficient of heat pipe is usually replaced with thermal conductivity as it is critical to evaluate the boiling and condensation of the working fluid. The thermal conductivity represents the overall behaviour of the heat pipe in transfering heat. Computational numerical analysis simplifies the structure of heat pipe without considering the internal design and modelling it as a solid copper rod. To determine the representative thermal conductivity of the wickless heat pipe, a computational numerical model of the TEM was developed. Experiment data of the TEM operation was used to validate the computational model where the cold-side air inlet temperature inlet was 20.7°C while the hot-side waste heat inlet temperature was 70.0°C. The representative thermal conductivity value for the wickless heat pipe was found to be 500 W/m.K in which the percentage difference for the hot-side and cold-side TEG surface temperatures, and the TEG surface temperature difference were below 5%. The approach was proven suitable to analyse the representative heat pipe thermal conductivity for simplified thermoelectric generator modules.